Initial evidence for the return of coronary vasoreactivity following the absorption of bioabsorbable magnesium alloy coronary stents. - Ghimire, G; Spiro, J; Kharbanda, R; Roughton, M; Barlis, P; Mason, M; Ilsley, C; Di Mario, C; Erbel, R; Waksman, R; Dalby, M (2009)
AIMS: To investigate the endothelium independent coronary smooth muscle vasomotor function four months after implantation of magnesium alloy absorbable metal stents (AMS) as part of the Progress-AMS clinical trial (n = 5), compared with a control group of patients implanted with permanent metal stents (PMS) (n = 10) undergoing follow-up angiography, but who were free from angiographic restenosis. METHODS AND RESULTS: Quantitative coronary angiogram (QCA) using an automated edge detection system was performed before and after the administration of 2 mg intracoronary isosorbide dinitrate (ISDN). The vessel diameter was measured at 0.2 mm intervals throughout the stented segments and a 1 cm proximal reference segment. The cross sectional area (CSA) was calculated before and after the ISDN, averaged and the percentage change measured. Reference segments demonstrated preserved vasomotor function in all cases: +13.28% (AMS) versus +17.15% (PMS), p = 0.39. The mean percentage increase in CSA for the stented segment was +6.78% for the AMS versus -1.30% for PMS, p = 0.003. CONCLUSION: These data demonstrate that four months after AMS implantation vasomotor function in reference segments is no different to that observed with PMS. However in contrast to PMS, within the AMS-stented segments there is demonstrable vasodilatation. These observations may have important implications for future stent design.